KETERGANTUNGAN GAME ONLINE FREE FIRE PADA ANAK SEKOLAH DASAR NEGERI 1 TELUK MELANO KECAMATAN SIMPANG HIIR KABUPATEN KAYONG UTARA - Ghufron nala (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2026)
This study aims to examine the impact of addiction to the online game Free Fire on the social behavior of children at SDN 1 Teluk Melano, Simpang Hilir District, Kayong Utara Regency. A qualitative descriptive method was employed, utilizing data collection techniques such as observation, interviews, and documentation. The findings indicate that addiction to Free Fire significantly affects students' social behavior, including their communication skills, cooperation abilities, and emotional regulation. The study recommends active involvement from parents and teachers in limiting gaming time and providing alternative activities that support children's social development.